Aortopexy for the treatment of tracheobronchomalacia in 100 children: a 10-year single-centre experience. (5th March 2018) - Rijnberg, Friso M; Butler, Colin R; Bieli, Christian; Kumar, Sonia; Nouraei, Reza; Asto, Joshua; McKavanagh, Eimear; de Coppi, Paolo; Muthialu, Nagarajan; Elliott, Martin J; Hewitt, Richard J
Abstract: OBJECTIVES: Our study describes and analyses the results from aortopexy for the treatment of airway malacia in children. METHODS: Demographic data, characteristics and preoperative, operative and outcome details, including the need for reintervention, were collected for children undergoing aortopexy between 2006 and 2016. RESULTS: One hundred patients [median age 8.2 months, interquartile range (IQR) 3.3–26.0 months] underwent aortopexy. Sixty-four (64%) patients had tracheomalacia (TM) only, 24 (24%) patients had TM extending into their bronchus (tracheobronchomalacia) and 11 (11%) patients had bronchomalacia. Forty-one (41%) children had gastro-oesophageal reflux disease, of which 17 (41%) children underwent a Nissen fundoplication. Twenty-eight (28%) children underwent a tracheo-oesophageal fistula repair prior to aortopexy (median 5.7 months, IQR 2.9–17.6 months). The median duration of follow-up was 5.3 years (IQR 2.9–7.5 years). Thirty-five (35%) patients were on mechanical ventilatory support before aortopexy. Twenty-seven (77%) patients could be safely weaned from ventilator support during the same admission after aortopexy (median 2 days, IQR 0–3 days). Fourteen patients required reintervention. Overall mortality was 16%. Multivariable analysis revealed preoperative ventilation ( P  = 0.004) and bronchial involvement ( P  = 0.004) to be adverse predictors of survival. Only bronchial involvement was a predictor for reintervention ( P  = 0.012). CONCLUSIONS: Aortopexy appears to be an effective procedure in the treatment of children with severe airway malacia. Bronchial involvement is associated with adverse outcome, and other procedures could be more suitable. For the treatment of severe airway malacia with isolated airway compression, we currently recommend aortopexy to be considered.